The clinical value of acupuncture for women with premature ovarian insufficiency: a systematic review and meta-analysis of randomized controlled trials - Cao, Hengjie; Li, Huize; Lin, Guangyao; Li, Xuanling; Liu, Shimin; Li, Peiqi; Cong, Chao; Xu, Lianwei (Frontiers in Endocrinology, 2024)
The aim of this study was to evaluate the therapeutic implications of acupuncture on improving ovarian function in women diagnosed with premature ovarian insufficiency (POI) through the implementation of randomized clinical trials (RCTs).A comprehensive search of eight databases was conducted to identify RCTs up until October 5, 2023. The outcomes included levels of sex hormones, antral follicle count (AFC), Kupperman score, and the total effective rate. The Risk of Bias (RoB) tool was utilized to evaluate the quality of the included studies. In order to guarantee robustness and reliability of the findings, subgroup and sensitivity analyses were performed to investigate potential sources of heterogeneity.Results: A total of 13 RCTs comprising 775 patients were included in the study. Acupuncture demonstrated significant efficacy in reducing follicle-stimulating hormone (FSH) (SMD = 0.83, 95% CI [0.27, 1.39], I 2 =92%, p = 0.004), enhancing estradiol levels (E2) (SMD = 0.50, 95% CI [0.07, 0.93], p = 0.02, I 2 = 87%), and increasing anti-Müllerian hormone (AMH) (SMD = 0.24, 95% CI [0.05, 0.44], p = 0.01, I 2 =8%), as well as improving the overall effective rate (RR = 1.22; 95% CI [1.10,1.35]; p < 0.01, I 2 =14%). Subgroup analysis revealed that compared to nonacupuncture therapy, the acupuncture with Chinese Herbal Medicine (CHM) and Hormone Replacement Therapy (HRT) group exhibited a substantial reduction in FSH levels (SMD = 1.02, 95%CI [0.52,1.51], I 2 =60%, p < 0.01). Furthermore, the acupuncture with CHM group also exhibited a substantial reduction (SMD = 4.59, 95%CI [1.53,7.65], I 2 =98%, p < 0.01). However, only the acupuncture with CHM and HRT group demonstrated a significant increase in E2 levels (SMD = 0.55, 95% CI [0.23, 0.87], I 2 =12%, p < 0.01).Acupuncture has demonstrated superiority over non-acupuncture in diminishing serum FSH levels, increasing serum E2, AMH, and the overall efficacy rate in women diagnosed with POI. These research findings suggest the necessity for broader-scale research with meticulous designs to fully demonstrate the the efficacy and safety of acupuncture in the treatment of women with POI.